Counselling and assistance in submitting MUI halal certification for MSMEs members of the North Lombok 'Aisyiyah regional leader - Putri, Dina Soes; Asmawati, -; Gunawan, Adi; Suwati, Suwati (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2023)
Free MUI Halal Certification (SEHATI) is one of the government's programmes to increase the amount of halal-labelled MSME products that can be exported to Muslim countries around the world. The SEHATI programme has been implemented since March 2022 and will be intensified in 2023 to achieve the target of 10 million halal certificates in 2024. One of the obstacles in the implementation of the SEHATI programme is the lack of socialisation, especially in the regions, so there are still many MSEs that have not been touched by this programme, for example in NTB. Therefore, the purpose of this service activity is to socialise the importance of Halal labelling on MSE products and to assist partners in applying for MUI Halal certification through the SEHATI programme. The stages of this activity are: initial data collection from MSEs, socialisation activities (counselling on the urgency of halal certification) and assistance in applying for halal certification of partner MSE products. Apart from the lack of knowledge of the partner members in terms of online administration, the main obstacle we face is the large number of MSEs that only use PDAM water (not yet halal certified) as a means of washing or production, so that only 5 MSEs out of a total of 15 MSEs supported by this service programme can obtain halal certificates.